Strategies to Overcome Digital Transformation Challenges in Courier Services - A Systematic Literature Review and Bibliometric Analysis - Marsita, Emay; Maniah, Maniah; Lestiani, Melia Eka (Dinasti International Journal of Education Management and Social Science, 2025)
The rapid evolution of digital technologies has fundamentally reshaped the courier industry, prompting a wave of innovations aimed at enhancing operational performance, customer experience, and environmental sustainability. This study adopts a Systematic Literature Review (SLR), integrated with bibliometric analysis, to examine 89 peer-reviewed articles indexed in Scopus from 2018 to 2025. The findings reveal four dominant strategic pathways adopted by courier service providers to navigate digital transformation: investing in digital culture (16%), building robust technological infrastructure (45%), securing financial resources (24%), and ensuring regulatory compliance (16%). The study also highlights a surge in research activity following the COVID-19 pandemic, reflecting an industry-wide urgency to modernize last-mile delivery operations. By synthesizing these insights, the research offers a conceptual framework for future strategic alignment and provides actionable guidance for courier firms facing the pressures of digital disruption.